V. Kapsukas ir spauda - Ulpis, Antanas (Knygotyra, 1972)
V. Mickevičius-Kapsukas, the famous worker of the Communist Party of Lithuania and the Communist International, an untiring fighter for the cause of the working class, did much for the development of the progressive press. He was an editor, editor-in-chief and a reviewer. Furthermore, he wrote many books, booklets and about 2000 articles which were printed in about eighty periodical editions. V. Kapsukas began taking part in the democratic press at the end of the 19th century. From the year 1903 he took an active part in the social democratic press, but soon he was disappointed in this action and became one of the first organizers of the revolutionary working and communist press in Lithuania. In this period of his life V. Kapsukas was an active participator of the Lithuanian Bolshevik newspaper, edited in Riga – Vilnis (“Wave”) and progressive press of the Lithuanian workers abroad: Rankpelnis (“Worker”), Kova (“Fight”), Naujoji gadynė (“The New Times”) and in other newspapers.V. Kapsukas had great services in the development of the Lithuanian communist press. He took an active part in the edition of the newspapers Tiesa (“Truth”), Komunistas (“Communist”), Kibirkštis (“Spark”), Komunaras (“Communar”), Balsas (“Voice”), Priekalas (“Anvil”), Krasnoje znamia (“Red Banner”), Zvezda (“Star”) and of many others as an organizer, edilor-in-chief, publicist or reviewer of these newspapers.He valued press from the point of view of the fighter for the working class, that is, how the press reacted to the political and social events and depicted the life of the working class and poor peasantry, how much it cared for their needs.The main points in V. Kapsukas biography as a press worker are fiction and literary critique. He was the first Lithuanian writer whose works without any doubt belonged to the Lithuanian proletarian literature.V. Kapsukas devoted all his life to the bright future of the working class. He was an active fighter against the bourgeois nationalist ideology and propagator of the ideas of internationalism and friendship among the peoples.